Language and Identity in the Contemporary Globalized World: A Sociolinguistic Analysis - Obaid, Rafal Hassoon (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study investigates the sociolinguistic relationship between language and identity in the context of globalization. In an era marked by rapid technological advancement and increased global interconnectedness, language not only facilitates communication but also serves as a crucial marker of personal, social, and cultural identity. The research explores how individuals and groups construct and negotiate identities through language use in multicultural and multilingual settings. Special attention is given to the impact of globalization on language ideologies, linguistic choices, and attitudes, particularly in digital spaces where traditional norms are both challenged and redefined. Using a sociolinguistic and discourse-analytic framework, the study examines how language functions as a dynamic resource for identity construction and how digital communication reshapes linguistic practices. It highlights how linguistic diversity and code-switching practices reflect evolving identity positions and power dynamics in global interactions. The findings underscore the dual role of digital media in both reinforcing linguistic hierarchies and providing spaces for marginalized voices to assert and reclaim their identities. This research contributes to theoretical and applied discussions in sociolinguistics, language policy, education, and intercultural communication. By emphasizing the role of language in identity formation, the study promotes a deeper understanding of how language practices shape social cohesion, cultural belonging, and mutual understanding in an increasingly diverse and interconnected world.